Fate of inorganic material during hydrothermal carbonisation of biomass: Influence of feedstock on combustion behaviour of hydrochar. (1st April 2016) - Smith, Aidan M.; Singh, Surjit; Ross, Andrew B.
Abstract: A series of high moisture content biomass have been processed by hydrothermal carbonisation (HTC) in a batch reactor at two temperatures (200 °C and 250 °C). The feedstocks processed include food waste, secondary sewage sludge, AD press cake, microalgae, macroalgae and a fibre derived from municipal derived wastes. In addition, three lignocellulosic biomass including miscanthus, willow and oak wood have been processed under identical conditions. The yields and properties of the resulting hydrochars including their HHV, CHNS, mineral content and ash fusibility properties have been determined and compared with their starting biomass. Typical char yields for lignocellulosic material range between 58 and 70 wt% at 200 °C and reduce to 40–46 wt% at 250 °C. The behaviour and mass balance is however very feedstock dependent and the higher lignin biomass produce higher yields of hydrochar. There is a significant upgrading of the energy density of the hydrochars with calculated HHV ranging from typically 24 MJ kg −1 at 200 °C to 28–31 MJ kg −1 at 250 °C for lignocellulosic material. The exception is for sewage sludge and AD press cake which result in a significant solubilisation of organic matter. A significant removal of alkali metals is observed and this in turn changes the ash chemistry upon combustion. This change in ash chemistry has been shown to change the ash melting behaviour and the hemisphere temperatures (oxidising conditions) were seen to increase substantially. A number of predictive slagging and fouling indices have been used to evaluate the influence of the ash chemistry on the fuel combustion behaviour and this combined with the ash fusion testing has shown that HTC reduces the potential fouling and slagging in some of the resulting hydrochars if combusted.